Perpetuating hegemony: a critical reflection on social forces shaping Mozambique’s development strategy. - Hansen, Mads Uhlin (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.